An account of a modified lightning protection system for power stations - Ahmad, Hussein; Ong, L. M. (2005)
Power stations may face huge losses and damage when struck by lightning. Much effort has been carried out to find an alternative to the conventional lightning air terminal for direct protection to power stations. One of the alternative is to modify the tip configuration of conventional air terminals to enable it to be better inceptor. This paper looks into such possibility by designing and testing different tip configuration air terminals, i.e. sharp, blunt, flat, conical and concave. Tests in high voltage laboratory revealed that blunt air terminal has lower breakdown voltage and longer time to breakdown compared to other air terminals. This suggests that the performance of blunt rod is better than other rods. Based on the laboratory experimental studies, the modification of air terminal geometrical tip could be an alternative for future application specifically for the lightning protection of power stations against direct strokes.